Conceiving Ecoptopia - Barnhill, David Landis (Journal for the Study of Religion, Nature and Culture, 2011)
Clarity of terminology is important in ecotopian studies. We can de?ne an ecotopian society as one that operates in interactive harmony with ecological systems, with humans and nonhuman nature mutually ?ourishing. The functions of ecotopia include critiquing contemporary society, stimulating ecotopian desire, and creating thought experiments about possible ecotopian societies. While many have noted the limitations of producing detailed and universal blueprints for a utopia, we can and should articulate positive content in ecotopian dreaming, which would give orientation to efforts toward an ecotopian horizon. The following principles provide a framework for ecotopianism while allowing for a wide diversity of ecotopian explorations: suf?ciency, high quality of life, egalitarianism, communitarianism, libertarianism, radical democracy, decentralization, appropriate technology, an af?rmation that the natural world has intrinsic value, a sense of identi?cation with nature, and a critique of the degradation of ecological systems.